2022
DOI: 10.1002/agj2.21042
|View full text |Cite
|
Sign up to set email alerts
|

Economics of reducing Palmer amaranth seed production in dicamba/glufosinate/glyphosate‐resistant soybean

Abstract: Increased prevalence of glyphosate-resistant (GR) weeds within agronomic cropping systems has led to the readoption of pre-emergence (PRE) herbicides and use of multiple herbicide-resistant soybean [Glycine max (L.) Merr.] cultivars. Herbicide programs were evaluated in the recently commercialized dicamba/glyphosate/glufosinate-resistant (DGGR) soybean for weed control, reduction of Palmer amaranth (Amaranthus palmeri S. Watson) seed production, crop safety, and economic performance. At 35 days after pre-emerg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 5 publications
(13 citation statements)
references
References 42 publications
0
10
0
Order By: Relevance
“…At 30 DAPRE, almost all residual herbicides recorded 1–3 plants m ‒2 apart from atrazine (15 plants m ‒2 ) and atrazine/bicyclopyone/mesotrione/ S ‐metolachlor (11 plants m ‒2 ). Striegel and Jhala (2022) reported that PRE herbicide reduced glyphosate‐resistant Palmer amaranth density to 0–1 plant m −2 compared with nontreated plots (26 plants m −2 ). Whitaker et al.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…At 30 DAPRE, almost all residual herbicides recorded 1–3 plants m ‒2 apart from atrazine (15 plants m ‒2 ) and atrazine/bicyclopyone/mesotrione/ S ‐metolachlor (11 plants m ‒2 ). Striegel and Jhala (2022) reported that PRE herbicide reduced glyphosate‐resistant Palmer amaranth density to 0–1 plant m −2 compared with nontreated plots (26 plants m −2 ). Whitaker et al.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, a PRE fb a POST herbicide program has a better chance of reducing MHR Palmer amaranth seed production compared with relying only on PRE herbicide. Striegel and Jhala (2022) reported that glyphosate‐resistant Palmer amaranth seed production declined to 0–325 seeds plant ‒1 when PRE herbicide was used compared with POST‐only programs (85–4786 seeds plant ‒1 ) in soybeans and further reduced to 0 seeds plant ‒1 when a PRE herbicide was followed by a POST herbicide with residual activity.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…More specifically, multi-tactic strategies that target multiple life stages of the weed, including understanding reproductive biology and potential for pollen-mediated gene flow, are required (Jhala et al 2021a(Jhala et al , 2021b. This can be accomplished by using an effective multiple-sites-of-action herbicide program, using cover crops, planting corn or soybean in narrow rows, using a harvest weed seed control method, and adopting diversified crop rotations (Mohler et al 2021;Striegel and Jhala 2022). The increasing use of HPPD-inhibitor herbicides in agronomic crops requires research on herbicide interactions and alternative herbicides or methods for controlling multiple herbicide-resistant weeds.…”
Section: Weed Technologymentioning
confidence: 99%